Design of a Multilayer Dual-Band Balanced Bandpass Filter on a Circular Patch Resonator - Xu, Yanhui; Liu, Zhengkang; Wang, Shiyan; Tang, Wanchun; Chen, Junxin (Frontiers in Physics, 2021)
This letter presents a novel multilayer dual-band balanced bandpass filter (BPD) design by using two perturbed circular patch resonators. TM11 mode and TM21 mode of the resonator with odd-symmetric field distributions are explored to realize the desired differential-mode (DM) transmission and common-mode (CM) suppression. Two circular patches are properly coupled in the back-to-back form to realize a dual-passband balanced response by virtue of coupling apertures etched on the ground. In addition to the internal coupling, the above apertures are also further utilized for the undesired degenerate mode harmonic suppression. Besides, slot perturbations on the patch are introduced to perturb TM21 resonant mode to independently adjust center frequency of the higher passband while the lower passband remain almost unchanged. Thus, two passbands can be flexibly controlled by simultaneously tuning the above slots and size of the patch. For validation, a dual-band balanced BPF prototype is implemented. Results indicate 18% and 26% wide fractional bandwidth centered at 5.5 GHz and 7.5 GHz with better than 20 dB return loss under DM operation and higher than 40 dB CM suppression over an ultra-wide frequency band.